COGNITIVE BEHAVIORAL COUNSELING STRESS INOCULATION TRAINING IN REDUCE BURNOUT FOR STUDENTS OF CLASS VIII SMPN 5 BANYUWANGI - Helmyana Ifani; Heriberthus Wicaksono (International Jurnal of Education Schoolars, 2021)
Education has an important role in the nation and state, building all potential resources that cover a very wide range of areas of life. The development of access and quality of education is a priority to build a more advanced nation. This study is a quasi-experimental (quasi-experimental), using the Non Equivalent Pretest-Posttest Control Group Design. It was chosen with the consideration that in a quasi-experiment, it is not possible to randomize the subject in the whole population group. Furthermore, pretest and posttest means giving tests to the subject before and after the treatment is given to each group. This design was chosen because this research is a therapeutic study to determine the effectiveness or effect of treatment on the dependent variable. Based on the results of research and discussion, it can be concluded that there is an effect of cognitive-behavioural counseling with Stress Inoculation Training on reducing burnout for class VIII students of SMP Negeri 5 Banyuwangi, with the results of 14,190 > 2,228. And there is also a difference in effectiveness between the experimental group that received treatment and the group that did not receive treatment in reducing the learning burnout of class VIII students of SMP Negeri 5 Banyuwangi, with the results 13,865≠7,416